2006
DOI: 10.1007/s10840-006-9045-1
|View full text |Cite
|
Sign up to set email alerts
|

The stepwise ablation approach for chronic atrial fibrillation—Evidence for a cumulative effect

Abstract: Treatment options for atrial fibrillation (AF) have evolved from simple, fluoroscopy-guided pulmonary vein isolation for those patients with paroxysmal AF to complex, multi-modality procedures targeting not only anatomic structures but also electrophysiologic phenomena including complex fractionated electrograms, sites of dominant frequency and local non-venous drivers in patients with persistent and permanent AF. The stepwise ablation approach is a novel technique whereby structures contributing to initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(145 citation statements)
references
References 43 publications
4
139
1
1
Order By: Relevance
“…3 In contrast, in a previous report, AF was termiKaplan-Meier event-free survival analysis was conducted to assess the cumulative freedom from AF recurrence using a cut-off of 43.5 mm for the LA diameter ( Figure 4B). The cumulative freedom from AF recurrence had a tendency to be greater in those with an LA diameter <43.5 mm than in those with an LA diameter ≥43.5 mm during 12±4.1 months of follow-up (65% vs. 42%; log-rank test, P=0.087).…”
Section: Af Termination By Ablationmentioning
confidence: 94%
See 2 more Smart Citations
“…3 In contrast, in a previous report, AF was termiKaplan-Meier event-free survival analysis was conducted to assess the cumulative freedom from AF recurrence using a cut-off of 43.5 mm for the LA diameter ( Figure 4B). The cumulative freedom from AF recurrence had a tendency to be greater in those with an LA diameter <43.5 mm than in those with an LA diameter ≥43.5 mm during 12±4.1 months of follow-up (65% vs. 42%; log-rank test, P=0.087).…”
Section: Af Termination By Ablationmentioning
confidence: 94%
“…As a predictor of successful termination of persistent AF, the measurement of the AF cycle length (CL) from the left atrial appendage (LAA) has been useful. 3 Further, as non-invasive pre-procedural predictors of the termination of persistent AF, the AFCL from the surface electrocardiogram (ECG) and duration of the continuous AF have been reported to be clinically useful as a pre-ablation tool for predicting the patients in whom SR can be restored by ablation. 5 Clinical prediction of the procedural and clinical outcomes of ablation in patients with persistent AF, however, have not been fully evaluated.…”
Section: Editorial P 1399mentioning
confidence: 99%
See 1 more Smart Citation
“…23, 24 In chronic AF, stepwise ablation of LA, including the pulmonary vein, roof line, CS, complex LA activities, and mitral isthmus, failed to terminate AF in 21% patients, suggesting that RA contributes, at least partially, to the maintenance of AF. 25 Meanwhile, Elayi et al reported that the bi-atrial ablation of a complex fragmented atrial electrogram has a minimal impact on AF termination during ablation. 26 However, the impact of the RA on the outcomes of AF after RFA is still controversial.…”
Section: Ra Enlargement Is An Independent Predictor Of Earlymentioning
confidence: 99%
“…In order to prevent such occurrences additional lesion sets were introduced: a left atrial roof line and a mitral isthmus line. More recently other procedures have been introduced as well, such as ablation of area showing CFAE and areas within the coronary sinus 31 or within the superior vena cava. 32 These additional lesion sets further increase the risk of gaps which in and of themselves provide channels that can allow macroreentrant atrial tachycardias or left atrial flutters to develop.…”
Section: Consequences Of Pvimentioning
confidence: 99%